Quality of dredged material in the river Seine basin (France). II. Micropollutants - Carpentier, S.; Moilleron, R.; Beltran, C.; Herve, D.; Thevenot, D. (Science of the Total Environment, 2002)
Dredging rivers is needed to ensure safe navigable waters, rivers and waterways. To anticipate the management of dredged materials in the case of the river Seine basin, the quality of the sediments in the river is checked every 3 years before dredging operations. The river Seine Basin is heavily submitted to pollution pressure from nearby industrial activities and urban expansion of Paris and its region. Here, the micropollutant content of the sediment sampled in 1996, 1999 and 2000 before dredging is discussed compared to regulatory standards. The results indicate that most of the sediment samples from the river Seine basin are lightly to moderately contaminated with organic and inorganic micropollutants (heavy metals, PAH, PCB), which makes the management after dredging easier. This pollution is strongly correlated with the organic matter content and to the fine fraction ( <50 mum) of the sediment. These results can lead to other management options than the ones already used in the river Seine basin: (1) dumping of lightly to moderately polluted sediments in quarries; and (2) physical treatment (sieving, hydrocycloning) of contaminated sediments issued from ’hot spots’. (C) 2002 Elsevier Science B.V. All rights reserved.